2021
DOI: 10.1038/s41598-021-83348-0
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a gene expression portrait of depression and its application for identifying potential treatments

Abstract: Depression is a complex mental health disorder and the goal here was to identify a consistent underlying portrait of expression that ranks all genes from most to least dysregulated and indicates direction of change relative to controls. Using large-scale neural gene expression depression datasets, a combined portrait (for men and women) was created along with one for men and one for women only. The depressed brain was characterized by a “hypo” state, that included downregulation of activity-related genes, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 79 publications
1
41
0
Order By: Relevance
“…CRH is associated with anxiety and arousal, has a nonlinear effect on behavior when acting among multiple receptors, and is associated with psychiatric disorders, including depression 20 23 . A number of activity related genes, EGR1, FOS, NR4A1, FOSB, and ARC, were downregulated in the model and depression and this is consistent with the idea of the depressed brain being in a 'hypo' state 11 . The upregulation of the cold-induced RNA binding protein (CIRBP) along with decreased expression of multiple heat shock proteins suggests a possible decreased CNS temperature.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…CRH is associated with anxiety and arousal, has a nonlinear effect on behavior when acting among multiple receptors, and is associated with psychiatric disorders, including depression 20 23 . A number of activity related genes, EGR1, FOS, NR4A1, FOSB, and ARC, were downregulated in the model and depression and this is consistent with the idea of the depressed brain being in a 'hypo' state 11 . The upregulation of the cold-induced RNA binding protein (CIRBP) along with decreased expression of multiple heat shock proteins suggests a possible decreased CNS temperature.…”
Section: Discussionsupporting
confidence: 85%
“…Further, possible models within the BxD recombinant inbred mice lines 48 as well as the collaborative cross mice 49 were not evaluated and it is possible that in future studies, a line with high congruence with depression will be identified. In this study a portrait of human depression was used that incorporated data from 29 human datasets from men and women across multiple brain regions and an advantage is that it provides a single consistent underlying signature of depression across the CNS for comparisons with the models 11 . The results from the separate analysis of the male and female portrait indicate both similarities and differences of matching to animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, a great deal of knowledge has been accumulated about the neurological mechanisms involved in depression, including the influence of inflammatory factors, the role of monoamines, and the influence of vascular disorders and genetics on the physiopathology of depression, regardless of environmental factors, eventually evolving to malfunction and/or damage to specific neural networks [ 7 , 8 , 9 , 10 , 11 ]. The datasets of gene regulation in depression is created and a combined portrait was created for men and women only [ 12 ]. Impairment of adult neurogenesis, altered nervous processes and synaptic depression, and neuronal atrophy are just some of the neuroplasticity-related processes that are at risk in patients with depression during clinical and experimental studies [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%